2020
DOI: 10.1158/1538-7445.sabcs19-ot1-08-04
|View full text |Cite
|
Sign up to set email alerts
|

Abstract OT1-08-04: A first-in-human phase Ia dose escalation study of GDC-0077, a p110a-selective and mutant-degrading PI3K inhibitor, in patients with PIK3CA-mutant solid tumors

Abstract: Background: Activating mutations in PIK3CA, encoding the p110α subunit of phosphatidylinositol 3-kinase (PI3K), are highly prevalent in breast cancer and solid tumor malignancies. GDC-0077 is a potent p110α-selective inhibitor with a novel mechanism of action that degrades mutant p110α and anti-tumor activity in PIK3CA-mutant breast cancer xenograft models as a single agent and in combination with anti-estrogens with or without a CDK4/6 inhibitor. An open-label, Phase I dose-escalation study of GDC-0077 monoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…With respect to the clinical relevance of our findings, a first-in-human, open-label, Phase I/IB dose escalation study of oral daily GDC-0077 alone and in combination with endocrine and targeted therapies for PIK3CA-mutant solid tumors is ongoing. The single-agent portion of the study showed that GDC-0077 had a manageable safety profile with a maximum tolerated dose of 9 mg once daily (supported by a linear pharmacokinetic profile), with promising anti-tumor activity (Juric et al, 2019). When combined at this dose with letrozole with and without palbociclib (Jhaveri et al, 2019), or when combined with fulvestrant the safety profile was also manageable with promising anti-tumor activity (Kalinsky et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the clinical relevance of our findings, a first-in-human, open-label, Phase I/IB dose escalation study of oral daily GDC-0077 alone and in combination with endocrine and targeted therapies for PIK3CA-mutant solid tumors is ongoing. The single-agent portion of the study showed that GDC-0077 had a manageable safety profile with a maximum tolerated dose of 9 mg once daily (supported by a linear pharmacokinetic profile), with promising anti-tumor activity (Juric et al, 2019). When combined at this dose with letrozole with and without palbociclib (Jhaveri et al, 2019), or when combined with fulvestrant the safety profile was also manageable with promising anti-tumor activity (Kalinsky et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While no adjuvant trials of alpelisib have been announced, these insights may be relevant as new PI3K inhibitors, such as GDC-0077 (inavolisib) which has increased selectivity for mutant p110α that may confer a greater therapeutic index, are developed. 43,44 A further consideration relevant to the use of predictive-biomarker guided therapies in early disease is the potential prognostic role of those biomarkers with standard adjuvant therapy, eg. whether they are associated with greater or lesser risk of recurrence with standard endocrine therapy (+/chemotherapy).…”
Section: Pi3k and Akt Inhibitorsmentioning
confidence: 99%
“…Particularly in the setting of early disease, focussing the development of targeted therapies on the critical sensitive population may justify treatment and permit maximization of strategies to maintain adherence. While no adjuvant trials of alpelisib have been announced, these insights may be relevant as new PI3K-inhibitors, such as GDC-0077 (inavolisib) which has increased selectivity for mutant p110α that may confer a greater therapeutic index, are developed [ 43 , 44 ].…”
Section: Pi3k and Akt Inhibitorsmentioning
confidence: 99%
“…GDC-0077, a PI3Kα inhibitor more selective towards mutant PI3K than wild-type PI3K, was found to induce proteasomal degradation of mutant PI3K, and caused tumor regression in PIK3CA -mutant breast cancer xenografts [ 115 , 116 ]. This compound is now in clinical trial (NCT03006172) as a single agent, as well as in combination with other TKIs and endocrine therapy for the treatment of PIK3CA-mutant solid tumors [ 117 ].…”
Section: Why Do We Need To Identify Novel Molecular Perturbations?mentioning
confidence: 99%